2012
DOI: 10.1016/j.jcmg.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Ischemic Memory Using Speckle Tracking Echocardiography

Abstract: Although abnormalities of PSS-related parameters alone persisted after recovery from 2-min occlusion, abnormalities of other deformation parameters, such as strain rate during early diastole, did not. These data suggest that assessment of PSS by speckle tracking echocardiography is useful for detecting myocardial ischemic memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 20 publications
6
63
1
2
Order By: Relevance
“…LV PSS is a marker of regional myocardial dysfunction and dyssynchrony in various diseases [23][24][25][26] induced by regional differences in timing and degree of contraction/loading. 13,27 There are few data on RV PSS.…”
Section: Relationship Between Early Septal Activation and Lateral Pssmentioning
confidence: 99%
“…LV PSS is a marker of regional myocardial dysfunction and dyssynchrony in various diseases [23][24][25][26] induced by regional differences in timing and degree of contraction/loading. 13,27 There are few data on RV PSS.…”
Section: Relationship Between Early Septal Activation and Lateral Pssmentioning
confidence: 99%
“…(Okuda et al , 2006, Pislaru et al , 2001, Voigt et al , 2003 Asanuma et al demonstrated use a canine model of coronary occlusion/reperfusion and showed that PSI significantly increased in the risk area until about 10 -20 min after coronary artery reperfusion, whereas PSS decreased in the risk area during occlusion but recovered to the baseline immediately after reperfusion. (Asanuma et al , 2012) Hosokawa et al demonstrated clinically that post-systolic shortening is a marker of recovery in patients with reperfused anterior myocardial infarction. (Hosokawa et al , 2000) Thus, post-systolic shortening has been shown to be useful for predicting reversible LV injury; however, little is known about the usefulness of PSI in the RV.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings provide an important insight into both reversible LV wall motion abnormality and transiently observed ECG characteristics of TTC. Myocardial strain analysis using speckle tracking echocardiography facilitates the detection of subtle myocardial motion, which is difficult to visualize with conventional echocardiography [5]. In layer specific analysis, PSS may persist for a longer period than during visually confirmed PSS [6].…”
Section: Discussionmentioning
confidence: 99%
“…Human rights statement All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2000 (5).…”
mentioning
confidence: 99%